Pelatihan Wawancara Kerja Dalam Bahasa Inggris Bagi Siswa SMK Menggunakan Metode Demonstrasi - Ubaedillah Ubaedillah; Damar Isti Pratiwi; Mukson Mukson; Rifatul Masrikhiyah; Laelia Nurpratiwiningsih (LPPM Universitas Muhadi Setiabudi, 2020)
In this period, the opportunity to get a job has been very competitive. Many companies only look for the highest quality human resources for recruiting new employees. The tendency to use international standards requires that prospective employees have high quality and competence in their fields. English language skills are a priority requirement for a company to choose human resources. English job interviews are a tool to test the English skills of job seekers. however, job interview skills are not widely taught in formal schools. But today an English job interview must be faced for every job seeker, especially in most large or foreign companies. Ma'arif Vocational School in Cirebon district has many students majoring office administration. After graduating from school they are prepared to work in companies. So, they need English language knowledge the skills to have an English job interview to get a job in a good place. The purpose of the program is English job interview training for 30 students of office administration department 12th grade at SMK Ma'arif using lecture and demonstration methods. This method contains tips and tricks for facing an English Job Interview using demonstration methods and a direct simulation of the English Job Interview process. Therefore this training has many advantages over their needs and it will be effective for their daily activities. This training also provides the main lesson for job interview questions that are frequently used and how to answer them. Using this training, it is hoped that they will have enough perspective, knowledge, and skills in dealing with job interviews at foreign companies